Covid-19 Outbreak and New Normal Policy to The Reaction of The Indonesian Capital Market: An Event Study Analysis - Milhah Alfionita; Dwi Cahyaningdyah (Management Analysis Journal, 2022)
This study aims to determine whether there is a difference in the average abnormal return on shares of the tourism, hotel, restaurant, transportation, and pharmaceutical sub-sectors before and after the outbreak of the Covid-19 pandemic and the implementation of the new normal policies in Indonesia. This research is quantitative research with an event study approach using a purposive sampling method to determine the number of samples. The study period was limited to 5 days before the event (t-5) and 5 days after the event (t+5). The test tool used in this research is the Wilcoxon signed rank test. The results of this study showed that during the announcement of the Covid-19 pandemic in Indonesia, there was a significant difference in the average abnormal return and no significant difference in the average trading volume activity in the shares of tourism, hotel, restaurant, and the pharmaceutical sub-sector. In addition, there was no significant difference in the average abnormal return and average trading volume activity in the transportation sub-sector shares. Meanwhile, the announcement of the new normal policies showed that there was no significant difference between the average abnormal return and average trading volume activity in the shares of tourism, hotel, restaurant sub-sector, and transportation sub-sector. Moreover, there was a significant difference between the average abnormal return and average trading volume activity in shares of the pharmaceutical sub-sector.